Fundamentals of entrepreneurship (ENT300) : Permata Borneo Furniture / Hadzna Ahmad ... [et al.] - Ahmad, Hadzna; Spencer, Eliza Dora; Shakawi, Nor Hidayu; Arin, Leeny Ejah (2012)
The business has been decided on the form of partnership. The partnership means here it is collaborations among members to form a successful business. The PERMATA BORNEO FURNITURE consists of four members. Each members will contributes certain amounts of money as agreed in our agreement. This business will start on 1 st January 2013.To explain more about the management of PERMATA BORNEO FURNITURE, all partners are entitled to participate in the business management of PERMATA BORNEO FURNITURE. After discussions among the partners of PERMATA BORNEO FURNITURE we have agreed and decide that Nor Hidayu binti Shakawi will become the General Manager and officially become Administration Manager. For Operational Manager, we have decided to appoint Eliza Dora Spencer, Hadzna binti Ahmad as our Marketing Manager and lastly Leeny Ejah anak Arin will become our Financial Manager.